2018
DOI: 10.1098/rsif.2018.0296
|View full text |Cite
|
Sign up to set email alerts
|

Individual preventive social distancing during an epidemic may have negative population-level outcomes

Abstract: The outbreak of an infectious disease in a human population can lead to individuals responding with preventive measures in an attempt to avoid getting infected. This leads to changes in contact patterns. However, as we show in this paper, rational behaviour at the individual level, such as social distancing from infectious contacts, may not always be beneficial for the population as a whole. We use epidemic network models to demonstrate the potential negative consequences at the population level. We take into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 26 publications
6
41
0
1
Order By: Relevance
“…Firstly, it observed that either proactive or reactive school closure found to be moderately effective in reducing the transmission of influenza and could only delay the peak of the pandemic by a week; [36]. The whole idea of the authors of this study is that rational preventive measures during epidemics could have a counter effect on the population in the long run as these measures might impact the behavioural changes of the public towards others, which could worsen the epidemic outcomes.…”
Section: Resultsmentioning
confidence: 89%
“…Firstly, it observed that either proactive or reactive school closure found to be moderately effective in reducing the transmission of influenza and could only delay the peak of the pandemic by a week; [36]. The whole idea of the authors of this study is that rational preventive measures during epidemics could have a counter effect on the population in the long run as these measures might impact the behavioural changes of the public towards others, which could worsen the epidemic outcomes.…”
Section: Resultsmentioning
confidence: 89%
“…Our results showed that early intervention of social distancing could reduce the epidemic size The results of virtual experiments vary. Some research suggested social distancing is effective, under the condition of early activation and long-lasting implement of combined measures [8], strict implement [6,9], and spontaneously adopted [10]; some concluded the effectiveness was mild [11]; some argued that moderate social distancing can worsen the disease outcome, [6,9] But real-world studies are rare. Here we quantified the impact of social distancing on the epidemic size in the real world, providing evidence that social distancing is effective to interrupt the transmission of the respiratory pathogen, especially with early implementation and to a substantial extent.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of non-pharmaceutical control measures requires further research to quantify their impact [3]. Mathematical models are useful to evaluate the possible effects on epidemic dynamics of preventive measures, and to improve decision-making in global health [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Kruse and Strack [2020], Atkeson [2020], Jones et al [2020], Glover et al [2020, Berger et al [2020], and Birge et al [2020]. More closely related are several papers endogenizing behavior and social distancing in the context of SIR models, such as Leung et al [2018], Toxvaerd [2020], Eichenbaum et al [2020], Farboodi et al [2020], and Maloney and Taskin [2020].…”
Section: Related Literaturementioning
confidence: 99%